Ceramic dielectric material as well as preparation method and application thereof

By using ceramic dielectric materials of barium titanate, modified montmorillonite and rare earth oxide in ceramic capacitors, the problem of easy cracking in ceramic capacitors during welding is solved, and the mechanical properties are improved while maintaining good electrical properties and stability.

CN119430911APending Publication Date: 2025-02-14SHANDONG SINOCERA FUNCTIONAL MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411613572.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When existing multi-layer ceramic capacitors are prone to cracking and failing due to mechanical stress during welding, and when adding additives to improve mechanical properties, electrical performance and stability are difficult to take into account.

Method used

Using a ceramic dielectric material, including barium titanate, modified montmorillonite and rare earth oxide, the flexural strength and bending resistance of ceramic capacitors are improved through the introduction of modified montmorillonite, while maintaining good electrical properties.

Benefits of technology

It improves the strength and bending resistance of ceramic capacitors, ensures the stability of electrical properties, and meets the dielectric temperature stability requirements of X7R.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131549970000081
    Figure BDA0005131549970000081
  • Figure BDA0005131549970000091
    Figure BDA0005131549970000091
Patent Text Reader

Abstract

The invention discloses a ceramic dielectric material as well as a preparation method and application thereof. The raw materials of the ceramic dielectric material comprise barium titanate, modified montmorillonite and rare earth oxide. The modified montmorillonite is added into the ceramic dielectric material, has a unique nano layered structure, and coats the surface of barium titanate after modification, so that the microstructure of the ceramic dielectric material is optimized, the strength and bending resistance of the MLCC are improved while the electrical properties of the MLCC are not affected, and the dielectric temperature stability meets the requirements of X7R.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic ceramic components, and in particular to a ceramic dielectric material and a preparation method and application thereof. Background Art

[0002] Multilayer ceramic capacitors (MLCCs) are widely used in communication infrastructure equipment circuits in the fields of communication equipment, automotive electronics, industrial machinery, medical equipment, etc. They can be used as power bypass capacitors, such as liquid crystal modules (liquid crystal drive voltage lines), high power supply voltage LSI / IC / OP amplifiers, or as smoothing capacitors, such as DC-DC converters (input and output), switching power supplies (secondary side), etc.

[0003] MLCC is an integral component made of ceramic materials and metal materials alternately stacked together, then pressed and co-fired. The ceramic materials mainly include ABO3 series ceramic materials (mainly BaTiO3), which are characterized by poor toughness, high brittleness and poor bending resistance. During the use of MLCC products, a problem often occurs: during the process of welding MLCC products on circuit boards, MLCC is easily affected by the mechanical stress of bending, resulting in cracking and failure. And if the mechanical properties of barium titanate ceramics are increased by adding certain additives, the ceramics obtained in this way cannot take into account good electrical properties and stability. Therefore, it is still necessary to find a barium titanate ceramic material that has good mechanical properties, electrical properties and stability. Summary of the invention

[0004] The object of the present invention is to provide a ceramic dielectric material that can improve the flexural strength and bending resistance of ceramic electronic components such as MLCC without affecting the electrical performance.

[0005] A first aspect of the present invention is to provide a ceramic dielectric material comprising barium titanate, modified montmorillonite and rare earth oxide.

[0006] Furthermore, the ceramic dielectric material includes the following components in molar proportions: 100 parts of barium titanate, 1 to 10 parts of modified montmorillonite, and 1 to 4 parts of rare earth oxides. The introduction of modified montmorillonite can improve the strength and bending resistance of MLCC while ensuring that the electrical properties of MLCC are not affected. When the addition amount of modified montmorillonite is less than 1 part, the strength and bending resistance do not meet the requirements. When the addition amount of modified montmorillonite is more than 10 parts, it will cause the deterioration of electrical properties.

[0007] Furthermore, the barium titanate particle size is 1-500nm.

[0008] Furthermore, the modified montmorillonite is modified by one or more elements of Mn, V, Ba, Ca, Co, Bi, Al, Nb, Zn, Sc, Y, Yb, Dy, Ho, and Er.

[0009] Furthermore, the modification method of the modified montmorillonite is an ion exchange method.

[0010] Furthermore, the modified montmorillonite comprises the following components in molar proportions: 100 parts of montmorillonite and 1 to 50 parts of modifying elements.

[0011] Furthermore, the rare earth oxide includes at least one oxide of Dy, Ho, Y, Yb, La, Ce, Er, and Gd.

[0012] Furthermore, the raw materials of the ceramic dielectric material also include a dispersant, a binder, a plasticizer, and a solvent.

[0013] Furthermore, the mass of the dispersant is 0.5% to 1% of the barium titanate.

[0014] Furthermore, the mass of the adhesive is 7% to 10% of the barium titanate.

[0015] Furthermore, the mass of the plasticizer is 2% to 4% of the barium titanate.

[0016] Furthermore, the mass of the solvent is 70% to 100% of the barium titanate.

[0017] Furthermore, the dispersant, adhesive, plasticizer, and solvent may be made of raw materials commonly used in the art. For example, the dispersant may include at least one of polyacrylamide salt and triethanolamine, the adhesive may include at least one of polyvinyl butyral resin and ethyl cellulose resin, the plasticizer may include at least one of dibutyl phthalate and polyethylene glycol, and the solvent may include at least one of toluene, anhydrous ethanol, butanone, and isopropanol.

[0018] The second aspect of the present invention is to provide a method for preparing a ceramic dielectric material, comprising the following steps: mixing raw materials of the ceramic dielectric material to obtain the ceramic dielectric material.

[0019] Furthermore, the mixing step includes grinding and dispersing steps, and a slurry-like ceramic dielectric material is formed through grinding and dispersing.

[0020] A third aspect of the present invention provides a ceramic capacitor comprising a ceramic dielectric layer, wherein the ceramic dielectric layer is sintered from the above ceramic dielectric material.

[0021] Furthermore, the ceramic capacitor is a semiconductor ceramic capacitor, a high voltage ceramic capacitor or an MLCC (multilayer ceramic capacitor), preferably an MLCC.

[0022] Furthermore, the sintering temperature is 1000-1500° C., preferably 1100-1300° C. The sintering time is 2-3 h (such as 2 h, 2.5 h, 3 h, etc.).

[0023] Furthermore, the sintering is carried out in an air atmosphere.

[0024] The fourth aspect of the present invention is to provide a method for preparing an MLCC, comprising the following steps:

[0025] Forming the ceramic dielectric material into a film to obtain a ceramic dielectric layer;

[0026] forming an internal electrode layer on the surface of the ceramic dielectric layer;

[0027] Stacking, pressing and sintering a plurality of ceramic dielectric layers whose surfaces form inner electrode layers to obtain a ceramic chip;

[0028] Electrodes are prepared at both ends of the ceramic chip to obtain MLCC.

[0029] Furthermore, the sintering temperature is 1000-1500° C., preferably 1100-1300° C. The sintering time is 2-3 hours.

[0030] Furthermore, the sintering is carried out in an air atmosphere.

[0031] Furthermore, the sintering step includes a binder removal step, that is, the pressed sample is heat treated to burn and remove the binder, plasticizer, etc. in the ceramic dielectric material. The heat treatment temperature is 250-350°C, and the heat treatment can be performed in the air atmosphere.

[0032] Furthermore, the method for forming the internal electrode layer on the surface of the ceramic dielectric layer can adopt a common method in the art, such as printing the internal electrode slurry on the surface of the ceramic dielectric layer to form the internal electrode layer. The thickness of the internal electrode layer and the internal electrode slurry can be selected according to actual needs.

[0033] Furthermore, the electrodes prepared at both ends of the ceramic chip can be electrodes commonly used in the art, such as silver electrodes or copper electrodes, etc., and their thickness can be selected according to actual needs.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] Modified montmorillonite is added to the ceramic dielectric material of the present invention. The material is a silicate sheet with a nanometer thickness, and the unit cell in its crystal structure is composed of two layers of silicon-oxygen tetrahedrons sandwiched between a layer of aluminum-oxygen octahedrons. After the montmorillonite is modified by one or more elements of Mn, V, Ba, Ca, Co, Bi, Al, Nb, Zn, Sc, Y, Yb, Dy, Ho, and Er, the modified elements enter the montmorillonite interlayer, effectively filling the interlayer gaps and improving the electrical properties of the montmorillonite. At the same time, the modified montmorillonite is coated on the surface of barium titanate to form a coating layer, which effectively improves the microstructure. Therefore, the electrical properties of the MLCC can be ensured to be unaffected while improving the strength and bending resistance of the MLCC, and the MLCC can have excellent durability, and the dielectric temperature stability meets the requirements of X7R. DETAILED DESCRIPTION

[0036] For ease of understanding of the present invention, the application will be described more fully below with reference to relevant embodiments. The following provides preferred embodiments of the application. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.

[0037] Example 1

[0038] The ceramic dielectric material includes the following components in molar proportions: 100 parts of barium titanate, 5 parts of modified montmorillonite (modified montmorillonite includes the following components in molar proportions: 100 parts of montmorillonite and 25 parts of Zn) and 3 parts of Dy2O3. The ceramic dielectric material also includes a dispersant polyamide salt accounting for 0.5% of the mass of the barium titanate, an adhesive PVB accounting for 7.0% of the mass of the barium titanate, a plasticizer polyethylene glycol accounting for 3% of the mass of the barium titanate and a solvent (toluene and anhydrous ethanol, m:m=1.0~1.5) accounting for 80% of the mass of the barium titanate.

[0039] Example 2

[0040] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, adding 1 part of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 5 parts of Mn) and 1 part of Ho2O3.

[0041] Example 3

[0042] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 10 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 10 parts of Ca) and 2 parts of Y2O3 are added.

[0043] Example 4

[0044] The difference from Example 1 lies in the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 7 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 15 parts of Ba) and 4 parts of Ce2O3 are added.

[0045] Example 5

[0046] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 3 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 30 parts of Bi) and 2.5 parts of Er2O3 are added.

[0047] Example 6

[0048] The difference from Example 1 lies in the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, adding 9 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 50 parts of Al) and 3.5 parts of Gd2O3.

[0049] Example 7

[0050] The difference from Example 1 lies in the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 6 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 40 parts of Nb) and 3 parts of Y2O3 are added.

[0051] Example 8

[0052] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, adding 2 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 35 parts of V) and 1.5 parts of Ce2O3.

[0053] Example 9

[0054] The difference from Example 1 lies in the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically: 8 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 20 parts of Sc) and 4 parts of Er2O3 are added.

[0055] Example 10

[0056] The difference from Example 1 lies in the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically: 4 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 45 parts of Y) and 2 parts of Gd2O3 are added.

[0057] Embodiment 11

[0058] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, adding 1 part of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 30 parts of Yb) and 1.5 parts of Dy2O3.

[0059] Example 12

[0060] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 4 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 30 parts of Dy) and 3 parts of Ho2O3 are added.

[0061] Embodiment 13

[0062] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, adding 9 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 40 parts of Ho) and 1.5 parts of Y2O3.

[0063] Embodiment 14

[0064] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 5 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite and 15 parts of Er) and 2.5 parts of Ce2O3 are added.

[0065] Embodiment 15

[0066] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, adding 2 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite, 15 parts of Ca and 20 parts of Sc) and 3 parts of Y2O3.

[0067] Example 16

[0068] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 10 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite, 20 parts of Al and 10 parts of Zn) and 2 parts of Ce2O3 are added.

[0069] Embodiment 17

[0070] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically: 3 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite, 30 parts of Co and 20 parts of Bi) and 3 parts of Er2O3 are added.

[0071] Embodiment 18

[0072] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 6 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite, 15 parts of Nb and 10 parts of Dy) and 1 part of Gd2O3 are added.

[0073] Embodiment 19

[0074] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 8 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite, 20 parts of Ho and 5 parts of Er) and 2.5 parts of Gd2O3 are added.

[0075] Embodiment 20

[0076] The difference from Example 1 is the content of modified montmorillonite, the modifying elements and the rare earth oxides, specifically, 7 parts of modified montmorillonite (the modified montmorillonite includes the following components in molar fractions: 100 parts of montmorillonite, 10 parts of Ca, 10 parts of Yb and 10 parts of Y) and 4 parts of Y2O3 are added.

[0077] Comparative Example 1

[0078] The difference from Example 1 is that no modified montmorillonite is added.

[0079] Comparative Example 2

[0080] The difference from Example 1 is that unmodified montmorillonite is added.

[0081] Comparative Example 3

[0082] The difference from Example 15 is that no modified montmorillonite is added.

[0083] Comparative Example 4

[0084] The difference from Example 16 is the content of modified montmorillonite. Specifically, 15 parts of modified montmorillonite are added.

[0085] Comparative Example 5

[0086] The difference from Example 20 is the content of modified montmorillonite. Specifically, 20 parts of modified montmorillonite are added.

[0087] Performance Testing

[0088] The ceramic dielectric materials in the embodiments and comparative examples are applied to prepare MLCC, comprising the following steps:

[0089] (1) Add barium titanate, modified montmorillonite, rare earth oxide, dispersant, binder, plasticizer and solvent into a sand mill, and disperse them through sand milling to form a slurry with good stability.

[0090] (2) The ceramic slurry is cast to form a thin film, which is then dried to obtain a 14 μm thick ceramic dielectric layer.

[0091] (3) A 2 μm thick silver-palladium inner electrode layer is formed on the surface of the ceramic dielectric layer obtained in step (2) by a printing process.

[0092] (4) The ceramic dielectric layers printed with the inner electrodes are stacked and then pressed into a block. After pressing, the blocks are cut into green pieces of a certain size.

[0093] (5) Debinding: The cut green embryos are debinded in an air debinding box at 280°C for 30 hours.

[0094] (6) Sintering: Then sinter at 1100°C for 2 hours in an air atmosphere to obtain a ceramic chip.

[0095] (5) Applying external electrode silver paste on both end surfaces of the ceramic chip and baking it at 900°C to form external metal electrodes;

[0096] The following methods are used to test the various performances of MLCC.

[0097] (1) Dielectric constant: The dielectric constant was calculated by using an automatic bridge tester under the following test conditions: voltage 1 V, frequency 1 kHz, temperature 25°C. The capacitance C was measured and the dielectric constant was calculated based on the sample size.

[0098] (2) Bending strength: Tested with a tensile tester, the product is welded on a dedicated PCB board, and a pressure of 1 mm / s is applied to the PCB board in the reverse direction until the capacity change rate of the product is greater than 10%, and the pressing distance (mm) is recorded. The greater the pressing distance, the stronger its bending resistance.

[0099] (3) Flexural strength: The product is fixed on the test bench mold using a tensile tester, and a pressure of 1 mm / s is applied to it using a tensile tester until the product breaks.

[0100] (4) Durability: Quantity: 10,000, temperature: 125°C, voltage: 1 times rated voltage, time: 1,000 h, record the number of MLCC failures.

[0101] The test results are shown in Table 1. As can be seen from Table 1, within the required range of the present invention, a dielectric material with excellent dielectric properties and reliability life can be obtained.

[0102] Table 1. MLCC performance test results

[0103]

[0104]

[0105] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A ceramic dielectric material, characterized in that: The ceramic dielectric material comprises the following components in molar proportions: 100 parts of barium titanate, 1 to 10 parts of modified montmorillonite and 1 to 4 parts of rare earth oxide.

2. The ceramic dielectric material according to claim 1, characterized in that The modified montmorillonite is modified by one or more elements selected from the group consisting of Mn, V, Ba, Ca, Co, Bi, Al, Nb, Zn, Sc, Y, Yb, Dy, Ho and Er; the modified montmorillonite comprises the following components in molar fractions: 100 parts of montmorillonite and 1 to 50 parts of the modifying element.

3. The ceramic dielectric material according to any one of claims 1 to 2, characterized in that: The modified montmorillonite is obtained by modification through an ion exchange method.

4. The ceramic dielectric material according to any one of claims 1 to 3, characterized in that: The rare earth oxide includes an oxide of at least one of Dy, Ho, Y, Yb, La, Ce, Er, and Gd.

5. The ceramic dielectric material according to any one of claims 1 to 4, characterized in that: The raw materials of the ceramic dielectric material also include a dispersant, a binder, a plasticizer, and a solvent.

6. The ceramic dielectric material according to any one of claims 1 to 5, characterized in that: The dispersant, adhesive, plasticizer and solvent may be made of raw materials commonly used in the art. For example, the dispersant may include at least one of polyacrylamide salt and triethanolamine, the adhesive may include at least one of polyvinyl butyral resin and ethyl cellulose resin, the plasticizer may include at least one of dibutyl phthalate and polyethylene glycol, and the solvent may include at least one of toluene, anhydrous ethanol, butanone and isopropanol.

7. The ceramic dielectric material according to any one of claims 1 to 6, characterized in that: The mass of the dispersant is 0.5% to 1% of the barium titanate; the mass of the adhesive is 7% to 10% of the barium titanate; the mass of the plasticizer is 2% to 4% of the barium titanate; and the mass of the solvent is 70% to 100% of the barium titanate.

8. The method for preparing the ceramic dielectric material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing raw materials of the ceramic dielectric material to obtain the ceramic dielectric material.

9. A chip-type multilayer ceramic capacitor, characterized in that: The dielectric layer thereof comprises the dielectric ceramic material according to any one of claims 1-7.

10. A method for preparing a chip-type multilayer ceramic capacitor, characterized in that: The method comprises the following steps: forming a film of the ceramic dielectric material according to any one of claims 1 to 7 to obtain a ceramic dielectric layer; forming an inner electrode layer on the surface of the ceramic dielectric layer; stacking, pressing and sintering a plurality of ceramic dielectric layers with inner electrode layers formed on their surfaces to obtain a ceramic chip; and preparing electrodes at both ends of the ceramic chip to obtain a chip-type multilayer ceramic capacitor.

Citation Information

Patent Citations

  • Chemical coating prepared base metal internal electrode multi-layer ceramic chip capacitor dielectric material

    CN101183610A

  • Montmorillonite ceramic filler composite modified dielectric elastomer as well as preparation method and application thereof

    CN114316364A

  • Flame-retardant soft PVC composite material and preparation method thereof

    CN114656726A

  • Dielectric ceramic material and chip multilayer ceramic capacitor prepared from same

    CN116425528A

  • Composite dielectric material

    JP2005302435A